2020
DOI: 10.3390/v12020200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Canine Histiocytic Sarcoma Cells Induced by an Infection with Canine Distemper Virus Led to a Dysregulation of HIF-1α Downstream Pathway Resulting in a Reduced Expression of VEGF-B In Vitro

Abstract: Histiocytic sarcomas represent malignant tumors which require new treatment strategies. Canine distemper virus (CDV) is a promising candidate due to its oncolytic features reported in a canine histiocytic sarcoma cell line (DH82 cells). Interestingly, the underlying mechanism might include a dysregulation of angiogenesis. Based on these findings, the aim of the present study was to investigate the impact of a persistent CDV-infection on oxidative stress mediated changes in the expression of hypoxia-inducible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…To date, the DH82 canine macrophage cell line has primarily been utilized as a model of viral and protozoan infection [23][24][25], such as for the study of canine distemper and its oncolytic potential [55][56][57]. Although studies have described the expression of functional P2 receptors in human or rodent macrophages and macrophage cell lines [8,10,11,34], studies directly investigating P2 receptors in canine macrophages have been absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the DH82 canine macrophage cell line has primarily been utilized as a model of viral and protozoan infection [23][24][25], such as for the study of canine distemper and its oncolytic potential [55][56][57]. Although studies have described the expression of functional P2 receptors in human or rodent macrophages and macrophage cell lines [8,10,11,34], studies directly investigating P2 receptors in canine macrophages have been absent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that DH82 cells express a number of macrophage markers, such as CD11c and CD18 [ 21 ], and can secrete tumour necrosis factor (TNF)-α and interleukin (IL)-6 similar to that observed in lipopolysaccharide (LPS)-stimulated canine monocytes [ 22 ]. Despite its use as an in vitro model of viral and protozoan infection [ 23 , 24 , 25 ], knowledge regarding purinergic signalling in DH82 cells is limited to a single report describing ATP- and adenosine-induced cytokine release [ 26 ]. Although this study did not investigate any purinergic receptor per se, DH82 cells represent a possible model to study endogenous P2 receptors in canine macrophages for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses appear to only suppress HIF-1α at the transcriptional level, in contrast to other oncolytic viruses that alter the proteasomal pathway to destabilise HIF-1α [18,31], or, as recently described, inhibit HIF-1α activity by preventing its nuclear localisation [32]. Even though HIF activity is mainly controlled by post-translational regulation, several studies highlight the contribution of HIF-1α mRNA expression towards hypoxia-specific gene expression [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The less pronounced effect in the present study lacking complete regression after intratumoral CDV infection might result from an inhibition of virus spread within the neoplastic tissue (<0.5% of tumor area infected) compared to typically high numbers of infected cells (>85%) in persistently infected cultures [ 34 , 45 ]. The mechanism of reduced angiogenesis might be addressed to an impairment of the hypoxia-inducible factor-1 α (HIF-1α) downstream pathway that resulted in a decreased vascular endothelial growth factor-B (VEGF-B) expression in persistently CDV-infected DH82 cells in vitro [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…94062922). Cultivation of DH82 cells for grafting was carried out in standard conditions as previously described [ 33 , 34 , 45 , 46 ]. To ensure maximum viability for grafting, cells were harvested at 70% to 80% confluence of the monolayer.…”
Section: Methodsmentioning
confidence: 99%